Cardiopulmonary Resuscitated Complications Encountered in Forensic Autopsy Cases: A 5-Year Retrospective Analysis in Ramathibodi Hospital - Tulyawit Wannasri; Vichan Peonim; Wisarn Worasuwannarak (Indian Journal of Forensic Medicine & Toxicology, 2021)
Purpose: This analysis considers the prevalence of internal organ injuries sustained from CPR in autopsied individuals who died from natural causes as well as correlations between internal organ injury and various potentially-related factors.Methods: This analysis is a descriptive retrospective study which makes use of filed autopsy reports of individuals who died of unnatural causes. Autopsies were carried out at the Forensic Pathology Laboratory between 2012 and 2016. Excluded individuals who died due to accident and sustained trauma or injury to chest and abdominal areas as well as individuals who were younger than 18. Results: This study comprised 154 individuals of which 122 males, and 32 females. Age distribution was between 18 and 82 years. This study found that injuries resulting from CPR administration were found in 83.11% of cases. The most frequent injury including ribs, sternum, and heart at 43.36%, 25.86%, and 10.33%, respectively. This study also found various types of abdominal and spine injury due to CPR. Statistical consideration of potentially correlated variables revealed that age was statistically significant (p=0.001) in relation to CPR, while sex and BMI were found to not exhibit statistically significant (p=0.203, p=0.351, respectively) in relation to CPRConclusion: Nature of CPR techniques it is possible that injury may be sustained to internal organs. It was seen that age have potential correlations with injury.